Parental Emotional Coaching untuk Meningkatkan Kemampuan Menghadapi Emosi Negatif Anak Tunarungu - Sarry, Septi Mayang; Ervika, Eka (Universitas Padjadjaran, 2018)
AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan kemampuan orangtua dalam menghadapi anak yang memiliki emosi negatif sebelum dan sesudah mengikuti program parental emotional coahing. Hasil dari penelitian ini menunjukan parental emotional coaching efektif bagi orangtua untuk meningkatkan kemampuan menghadapi emosi negatif anak tunarungu. Penelitian ini merupakan quasi eksperimen yang diukur dengan Coping with Childrenâs Emotion Scale (CCNES) dari Fabes dan koleganya (1990-an) yang mengambarkan 6 respon orangtua dalam menghadapi emosi negatif anak yaitu problem focused reaction, emotion focused reaction, expressive encouragement, minimization reaction, punitive reaction, distress reaction. Dua respon pertama yaitu, problem focused reaction, emotion focused reaction merupakan suatu respon yang mendukung untuk bisa menghadapi emosi negatif anak secara efektif. Modul program parental emotional coaching disusun berdasarkan teori Gottman (dalam Cook, 2004).Â AbstractThis research aimed to determine differences in the ability of parents in dealing with children with hearing negative emotions before and after parental emotional coaching program. Parental emotional coaching aimed to coach parents come be a emotional coacher in dealing childrenâs negative emotion. Measurements were made with Coping with Childrens Emotion Scale (CCNEs ) of Fabes and colleagues ( 1990 ) describing 6 responses of parents in dealing with negative emotions children are problem focused reaction, emotion focused reaction, expressive encouragement, minimization reaction, punitive reaction, distress reaction. The first two responses , namely , reaction problem focused , emotion focused reaction is a response to support the child could face negative emotions effectively . Parental emotional coaching program modules compiled based on Gottman s theory ( in Cook , 2004). This research use quasi experiment design. The results of this study indicate that parental emotional coaching effectively to improve the ability to deal with negative emotions deaf children.